Compact Brillouin Fiber Laser Based on Highly Nonlinear Fiber With 51 Double Spacing Channels - Ahmad, B.A.; Al-Alimi, A.W.; Abas, Ahmad Fauzi; Mokhtar, Makhfudzah; Harun, Sulaiman Wadi; Mahdi, Mohd Adzir (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A compact multiwavelength Brillouin fiber laser (BFL) with 51 stable double Brillouin frequency shift channels is demonstrated at room temperature. It uses a ring cavity with a 3-dB coupler for separation of odd-ordered and even-ordered Brillouin Stokes (BS) channels using a highly nonlinear fiber (HNLF) as the Brillouin gain medium. Compared with the use of a standard single-mode fiber, the HNLF-based BFL produces higher output power and a higher count of Stokes lines. At the maximum Brillouin pump (BP) power of 16.7 dBm, 36 odd channels and 15 even channels are generated with a channel spacing of 0.15 nm. The output power of the even channels is observed to be always lower than that of the odd channels as they are generated from the previous odd BS.